Unraveling the harmful effect of oxidative stress on male fertility: A mechanistic insight - Hussain, Tarique; Kandeel, Mahmoud; Metwally, Elsayed; Murtaza, Ghulam; Kalhoro, Dildar Hussain; Yin, Yulong; Tan, Bie; Chughtai, Muhammad Ismail; Yaseen, Anjaleena; Afzal, Ali; Kalhoro, Muhammad Saleem (Frontiers in Endocrinology, 2023)
Male infertility is a widely debated issue that affects males globally. There are several mechanisms involved. Oxidative stress is accepted to be the main contributing factor, with sperm quality and quantity affected by the overproduction of free radicals. Excess reactive oxygen species (ROS) cannot be controlled by the antioxidant system and, thus, potentially impact male fertility and hamper sperm quality parameters. Mitochondria are the driving force of sperm motility; irregularities in their function may lead to apoptosis, alterations to signaling pathway function, and, ultimately, compromised fertility. Moreover, it has been observed that the prevalence of inflammation may arrest sperm function and the production of cytokines triggered by the overproduction of ROS. Further, oxidative stress interacts with seminal plasma proteomes that influence male fertility. Enhanced ROS production disturbs the cellular constituents, particularly DNA, and sperms are unable to impregnate the ovum. Here, we review the latest information to better understand the relationship between oxidative stress and male infertility, the role of mitochondria, the cellular response, inflammation and fertility, and the interaction of seminal plasma proteomes with oxidative stress, as well as highlight the influence of oxidative stress on hormones; collectively, all of these factors are assumed to be important for the regulation of male infertility. This article may help improve our understanding of male infertility and the strategies to prevent it.